2017
DOI: 10.1002/osp4.118
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent reductions in body weight during the Beef WISE Study: beef's role in weight improvement, satisfaction and energy

Abstract: SummaryObjectiveThe objective of this randomized equivalence trial was to determine the impact of consuming lean beef as part of a high protein (HP) weight‐reducing diet on changes in body weight, body composition and cardiometabolic health.MethodsA total of 120 adults (99 female) with overweight or obesity (BMI: 35.7 ± 7.0 kg m−2) were randomly assigned to consume either a HP diet with ≥4 weekly servings of lean beef (B; n = 60) or a HP diet restricted in all red meats (NB; n = 60) during a 16‐week weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 37 publications
6
28
0
Order By: Relevance
“…Subjects were randomly assigned to one of two energy-restricted diets: A HP diet with instructions to consume ≥4 weekly servings of lean beef as the only source of red meat (B), or a HP diet with instructions not to consume any red meat for the duration of the study (NB). The details of the weight loss intervention were previously published [ 29 ]. Briefly, all subjects participated in the State of Slim (SOS) group-based weight management program [ 31 ] at the AHWC for 16 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subjects were randomly assigned to one of two energy-restricted diets: A HP diet with instructions to consume ≥4 weekly servings of lean beef as the only source of red meat (B), or a HP diet with instructions not to consume any red meat for the duration of the study (NB). The details of the weight loss intervention were previously published [ 29 ]. Briefly, all subjects participated in the State of Slim (SOS) group-based weight management program [ 31 ] at the AHWC for 16 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The exact macronutrient distribution of the SOS diet plan is variable among participants (depends on specific chosen foods) and the 3 diet phases. Estimated macronutrient distributions for the SOS diet plan have been calculated and previously reported to be 26–32% carbohydrate, 40–50% protein, and 24–28% fat [ 29 ]. Protein foods in the SOS program are lean and minimally processed (i.e., lean meat and poultry, fish, egg whites, and fat-free dairy) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher protein (HP) diets may help with weight loss by increasing satiety, increasing energy expenditure and promoting greater loss of fat vs. fat-free mass compared with lower or normal protein diets that provide dietary protein at or near the current Recommended Daily Allowance of 0.8 g of protein per kg of body weight (1)(2)(3)(4). It was previously reported that a HP diet that included lean beef was as effective as a HP diet without beef in producing weight loss while preserving fat free mass and improving cardiometabolic health (5). Whether weight loss is impacted by the source of protein has not be exhaustively studied, and some evidence indicates that proteins from animal vs. plant sources may differentially impact appetite and eating behaviour (6).…”
Section: Introductionmentioning
confidence: 99%